1998
DOI: 10.1001/jama.279.24.1962
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Gluconate Lozenges for Treating the Common Cold in Children

Abstract: Context.-The common cold is one of the most frequently occurring illnesses and is responsible for substantial morbidity and economic loss. Biochemical evidence suggests that zinc may be an effective treatment, and zinc gluconate glycine (ZGG) lozenges have been shown to reduce the duration of cold symptoms in adults. Objective.-To determine the efficacy of ZGG treatment of colds in children and adolescents. Design.-A randomized, double-masked, placebo-controlled study. Setting.-Two suburban school districts in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(87 citation statements)
references
References 33 publications
0
86
0
1
Order By: Relevance
“…To address concerns over potentially inadequate blinding to the taste of the placebo, we conducted a post hoc sensitivity analysis in which we excluded trials that reported significant differences in bad taste between zinc and placebo arms 33,34 or did not report a bad taste outcome. 30,35 After excluding these trials, the duration of cold symptoms still favoured zinc, with a …”
Section: Duration Of Symptomsmentioning
confidence: 99%
See 3 more Smart Citations
“…To address concerns over potentially inadequate blinding to the taste of the placebo, we conducted a post hoc sensitivity analysis in which we excluded trials that reported significant differences in bad taste between zinc and placebo arms 33,34 or did not report a bad taste outcome. 30,35 After excluding these trials, the duration of cold symptoms still favoured zinc, with a …”
Section: Duration Of Symptomsmentioning
confidence: 99%
“…Heterogeneity: I² = 82% Children Kurugöl et al 31 Kurugöl et al 32 Macknin et al 33 Subtotal Heterogeneity: I² = 84%…”
Section: Favours Placebomentioning
confidence: 99%
See 2 more Smart Citations
“…Postulated mechanisms in the common cold include interfering with rhinovirus protein cleavage or capsid binding to ICAM-1 in nasal epithelium (Novick, Godfrey et al 1996). Zinc lozenges appeared to have positive effects on adults but negative effects on children in terms of duration and severity of common cold symptoms (Macknin, Piedmonte et al 1998;Marshall 2000). Higher doses were found to have a greater impact in reduction of symptom duration and reduced symptom severity (Godfrey, Conant Sloane et al 1992;Mossad, Macknin et al 1996).…”
Section: Prevention and Treatment For Respiratory Virusesmentioning
confidence: 99%